Method and Technology of Green Coal Mining (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The green mining of coal resources aims to realize the best economic and environmental benefits in the process of coal resource development, which is relevant to the sustainable development of the earth. Green mining technologies include the following: water-preserved mining for water resource protection; filling mining for the protection of the earth and buildings; simultaneous extraction of coal and gas for the realization of gas discharge; intelligent green mining to realize emission reduction; clean energy development in mining enterprises for the realization of resource transformation; and water and soil ecological restoration for the ecological protection of mining areas.